OPTIMAL TRACKING AND REGULATION ACCURACY OF FEEDBACK CONTROL SYSTEMS - T. BAKHTIAR (MILANG Journal of Mathematics and Its Applications, 2005)
This paper deals with intrinsic performance limits achievable by feedback control. We give analytical expressions of the optimal tracking and regulation problems for linear shift- invariant single-input and multiple-output (SIMO) discrete-time systems. For the former, we modify the existing results by means of the delta operator and show that the continuous-time counter- part results can be properly recovered from this point. For the latter, we derive a discrete-time result ﬁrst and show the conver- gence property.